Livelihood trajectory simulation model tool - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The simulation modelling capability to combine globally calibrated crop models (APSIM) with inuitive models of system interactions causing livelihood impacts (Simile) engineered in 2020 has been shown to produce useful results in predicting impacts of innovations on farm households in Kenya and Ethiopia in 2021